KONDISI TENAGA KERJA PENYANDANG DISABILITAS : TANTANGAN DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS - Winsherly Tan (Trunojoyo Madura University, 2021)
Sustainable development or commonly called Sustainable Development Goals (SDGs) is a goal achieved by many countries, including Indonesia. One of the goals of the SDGs is to create jobs for all parties without exception. Then the principle used in the SDGs is